Massive In Vitro Propagation Of Sandalwood Through Friable Embryogenic Callus - Supatmi, Supatmi; Ardiyanti, Nurdiya; Rahman, Nurhamidar; Sudarmonowati, Enny (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2016)
Sandalwood (Santalum album), which belongs to Santalaceae family, is a commercially important tree in Indonesia due to its many application. However,its population has significantly depleted since the planting materials using conventional methods are difficult to be provided. This study was conducted to mass propagate sandalwood using in vitro methods through friable embryogenic callus (FEC). The somatic embryos were formed using leaves cultured in MS +0.5 mg/l +1 mg/l indole acetic acid (IAA), and MS +1 mg/l IAA + 0.2 mg/l kinetin as well as 0.5 MS+1 mg/l Gibberellic acid (GA3). Primary somatic embryos (PSE) and secondary somatic embryos (SSE) then formed friable embryogenic callus when they were repetitively transferred to MS +1.5 mg/l BAP + 1.2 mg/l kinetin every 3 weeks. The maturation and regeneration of FEC was best done in the MS +1.5 mg/l BAP + 1.2 mg/l kinetin for 4-8 weeks. The acclimatization of sandalwood plantlets can be best conducted in the medium containing soil, sand and compos in ratio of 1:1:1 with the companion plant Murraya paniculata, which gave the best percentage of survival rate and the lowest percentage of falling leaves.